Autoimmune uveitis attenuated in diabetic mice through imbalance of Th1/Th17 differentiation via suppression of AP-1 signaling pathway in Th cells - Takeuchi, Masaru; Nishio, Yoshiaki; Someya, Hideaki; Sato, Tomohito; Yoshimura, Akihiko; Ito, Masataka; Harimoto, Kozo (Frontiers in Immunology, 2024)
Purpose Inflammation is involved in the pathogenesis of diabetes, however the impact of diabetes on organ-specific autoimmune diseases remains unexplored. Experimental autoimmune uveoretinitis (EAU) is a widely accepted animal model of human endogenous uveitis. In this study, we investigated the effects of diabetic conditions on the development of EAU using a mouse diabetes model. Methods EAU was induced in wild-type C57BL/6 (WT) mice and Ins2Akita (Akita) mice with spontaneous diabetes by immunization with IRBP peptide. Clinical and histopathological examinations, and analysis of T cell activation state were conducted. In addition, alternations in the composition of immune cell types and gene expression profiles of relevant immune functions were identified using single-cell RNA sequencing. Results The development of EAU was significantly attenuated in immunized Akita (Akita-EAU) mice compared with immunized WT (WT-EAU) mice, although T cells were fully activated in Akita-EAU mice, and the differentiation into Th17 cells and regulatory T (Treg) cells was promoted. However, Th1 cell differentiation was inhibited in Akita-EAU mice, and single-cell analysis indicated that gene expression associated AP-1 signaling pathway (JUN, FOS, and FOSB) was downregulated not only in Th1 cells but also in Th17, and Treg cells in Akita-EAU mice at the onset of EAU. Conclusions In diabetic mice, EAU was significantly attenuated. This was related to selective inhibition of Th1 cell differentiation and downregulated AP-1 signaling pathway in both Th1 and Th17 cells.